2013
DOI: 10.3758/s13421-012-0281-6
|View full text |Cite
|
Sign up to set email alerts
|

Major memory for microblogs

Abstract: Online social networking is vastly popular and permits its members to post their thoughts as microblogs, an opportunity that people exploit, on Facebook alone, over 30 million times an hour. Such trivial ephemera, one might think, should vanish quickly from memory; conversely, they may comprise the sort of information that our memories are tuned to recognize, if that which we readily generate, we also readily store. In the first two experiments, participants' memory for Facebook posts was found to be strikingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 21 publications
(14 reference statements)
6
48
0
Order By: Relevance
“…The popularity of social media makes it increasingly important to understand how engaging with this type of media shapes cognition. Previous research suggests that memory for social media content is high among the general population: Memory for Facebook microblogs is significantly higher than memory for sentences from books, news headlines, and even human faces (Mickes et al, 2013). The popularity of health-and dieting-related content on Instagram in particular emphasizes the importance of understanding how the act of viewing and interacting with these images impacts the viewer.…”
Section: Introductionmentioning
confidence: 99%
“…The popularity of social media makes it increasingly important to understand how engaging with this type of media shapes cognition. Previous research suggests that memory for social media content is high among the general population: Memory for Facebook microblogs is significantly higher than memory for sentences from books, news headlines, and even human faces (Mickes et al, 2013). The popularity of health-and dieting-related content on Instagram in particular emphasizes the importance of understanding how the act of viewing and interacting with these images impacts the viewer.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Mickes et al (2013) found that younger adults had a robust memory for social media content. In their study, college-aged participants were presented with faces, book sentences, or Facebook posts.…”
mentioning
confidence: 95%
“…However, Mickes et al (2013) did not examine the impact of knowing the source of the items. In their study, all items were presented without any source identifiers (i.e., as typed sentences).…”
mentioning
confidence: 99%
“…A second major challenge in opinion formation is understanding how social risk diffusion responds to the reintroduction of balanced information, which is often the hallmark of expert opinion (Tetlock, 2010). Various psychological biases influence memory and social message transmission, such as enhanced retrieval for personal information and anecdotes, and selection for more easily communicated information (Kirby, 2001;Kirby, Cornish, & Smith, 2008;Mickes et al, 2013), all of which may limit the ability of balanced accounts to correct social risk amplification. Higher anxiety promotes selective processing and is therefore associated with less risk attenuation in response to balanced information (Mathews, 1990;Mathews & Mackintosh, 1998).…”
Section: Introductionmentioning
confidence: 99%